Does Worker Well-Being Adapt to a Pandemic? An Event Study Based on High-Frequency Panel Data - Julia Schmidtke; Clemens Hetschko; Ronnie Schöb; Gesine Stephan; Michael Eid; Mario Lawes (Review of Income and Wealth, 2023)
We estimate the dynamic impact of two waves of the COVID-19 pandemic on an exceptionally broad range of indicators of worker well-being. Our analyses are based on high-frequency panel data from an app-based survey of German workers and employ an event-study design with individual-specific fixed effects. We find that workers' mental health decreased substantially during the first wave of the pandemic. To a smaller extent, this is also true for life satisfaction and momentary happiness. Most well-being indicators converged to prepandemic levels when infection rates declined. During the second wave of the pandemic, overall worker well-being decreased less than that during the first wave. Life satisfaction does not seem to have changed at all. We conclude that worker well-being adapts to the pandemic. Moreover, subgroup analyses indicate that, in terms of well-being, workers who took part in a job retention scheme fared less well during the pandemic than other employees.
Keywords: 330; adaptation; COVID-19 pandemic; job retention scheme; mental health; well-being